Prospects for the development of the rural areas of Poland – selected issues - Bański, Jerzy (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2014)
The primary objective of the study is to identify the development prospects for the Polish countryside in the subsequent decades. The author has identified the most important of so-called „megatrends” which affect the future picture of Poland. These have included: globalisation, expansion of new economic powers, localism, demographic polarization, transformation of the natural environment, diversification of energy sources, and the growth of information and a knowledge-based society. In the following part of the paper he discusses the most important contemporary processes and phenomena of the social, economic and environmental issues in the rural areas that will shape the future of the Polish countryside. The image of rural areas in the next 20–30 years will probably not radically change, but it can be argued that it will be more diverse, more active and more attractive.
Keywords: Rural areas; Poland; trends; the future of countryside; socio-economical changes